2019
DOI: 10.2478/jomb-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory and hemostatic cardiovascular risk markers during acute hyperglycemic crisis in type 1 and type 2 diabetes

Abstract: Summary Background We analyzed cardiovascular inflammatory (C-reactive protein (CRP), interleukin 6 (IL-6)), haemostatic (homocysteine) risk markers in lean and obese patients at admission and acute hyperglicemic crisis (AHC) resolving, involving diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS). Methods In that context, we included group A: N = 20 obese, B: N=20 lean patients with DKA; C: N = l0 obese, D: N=10 lean patients with HHS; E: N = 15 obese, F: N=15 lean controls. CRP IL-6, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
2
12
1
1
Order By: Relevance
“…This suggests that low-dose insulin combined with electrolytes can improve the inflammatory response in children with DKA. In the study of Popovic et al (31), the levels of inflammatory factors CRP and IL-6 in DKA patients after intravenous insulin therapy were significantly decreased, which is similar to our study. This suggests that low-dose insulin combined with electrolyte therapy is related to the alleviation of inflammatory response.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that low-dose insulin combined with electrolytes can improve the inflammatory response in children with DKA. In the study of Popovic et al (31), the levels of inflammatory factors CRP and IL-6 in DKA patients after intravenous insulin therapy were significantly decreased, which is similar to our study. This suggests that low-dose insulin combined with electrolyte therapy is related to the alleviation of inflammatory response.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, there was a significant decrease of CRP levels in patients with DKA without infection after improvement of the Acute illness in comparison to its levels at time of admission (P = 0.054) was still higher than the CRP levels determined in control subjects with mean ± SD (17.13 ± 24.66, 2.02 ± 1.25) respectively matching with a study done by Dragana et al 2019 [15].…”
Section: Discussionsupporting
confidence: 88%
“…Microalbuminuria was previously considered s a gold standard in early detection of DN despite being a non-specific marker, concomitantly present in other pathological conditions such as urinary tract infections, cardiovascular disease, in non-diabetic patients, etc. In addition, the body of evidence indicates a high percentage of patients with T2DM, who have renal involvement despite the absence of microalbuminuria (5,6). Studies have shown a progressive decline in the number of podocytes and disappearance of foot processes which occur in the early stages of DN due to apoptosis or shedding of podocytes.…”
Section: Introductionmentioning
confidence: 99%